Benefits obtained with the tele dermatology consultation in Guerrero Negro Baja California Sur. - Talamantes, Azucena Aribel; Alvarez Villaseñor, Andrea Socorro; Ibarra Urzua. , Haydee; Garcia Valdez, Ruth (Horizonte Sanitario, 2021)
Introduction: The term Tele dermatology (TD) is defined as “information and telecommunication technology to provide dermatological services at a distance”. Multiple studies have certified the reliability and applicability of this tool and its cost-effectiveness. This strategy is evaluated through indicators such as savings achieved and waiting time. In Baja California Sur there is a dermatologist who cares for the entire area. General Objective: Identify and describe the benefits in savings achieved and deferred duration of dermatology teleconsultation in patients treated in Guerrero Negro, Baja California Sur. Material and methods: Observational study of cost effectiveness. Fifty-eight files of patients treated at the dermatology teleconsultation in Guerrero Negro were reviewed. Demographic variables, reason for care, referral unit, savings achieved, and waiting time were analyzed. Study without risk. It was authorized by the ethics and research committee. Results: 81.6% were women, 29.3% from 31 to 50 years old, 24.1% housewives, the main diagnosis was dermatosis, and 50% belonged to Family Medicine Unit No. 35. The real time in hours to obtain a tele consultation vs face-to-face consultation was 638.50 + 879.05 vs 1,165.71 + 671.69 (p = 0.000; 95% CI 0.000 - 0.050). The cost in Mexican pesos of the transfer of the teleconsultation versus face-to-face consultation was compared 302.08 ± 695.62 vs 5,014 ± 5,377.28 (p = 0.003 95% CI 0.000 - 0.050) Conclusions: In this study, the teledermatology strategy was cost effective, it benefited mainly to women between 31 and 50 years old, housewives with a diagnosis of dermatosis, whose main assignment was the Family Medicine Unit No. 35 in Guerrero Negro, to a lesser extent than the medical units geographically located on islands. Keywords: Tele-consultation, savings achieved, deferred time of consultation, Tele-dermatology.